Numerical investigation on performance and emission characteristics of a diesel engine fired with methanol blended diesel fuel / Gurkamal Nain Singh...[et al.] - Singh, Gurkamal Nain; Bharj, Rabinder Singh; Kumar, Rajan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The effects of methanol and oleic acid blended diesel fuel on the performance and emissions of the diesel engine are evaluated numerically by commercial software Diesel-RK to simulate a single cylinder, naturally aspirated, direct injection, four-stroke diesel engine. The present study also resolves the problem of the immiscibility of methanol in diesel fuel, as to avoid immiscible nature an optimum percentage of oleic acid and n-butanol is added to make blends stable. The methanol blended diesel fuels are 7%, 12%, and 17% methanol in volume basis (D85M7NB1O7, D75M12NB1O12, and D65M17NB1O17). A drastic reduction in NOx emission is observed due to low combustion temperature however the PM emissions increases which can be controlled by using exhaust after-treatment techniques. The results indicate that: the brake specific fuel consumption increases and brake thermal efficiency decreases with an increase of methanol, oleic acid and n-butanol contents in the blended fuel whereas maximum heat release rate increases and exhaust temperature decreases.